Flasher: Exploring the Mind of an Exhibitionist - Patricia Amanda (Institute of Research and Community Outreach - Petra Christian University, 2018)
Exhibitionism is a mental disorder characterized by compulsive disorder for exhibiting genital to an unsuspecting stranger. Through my creative work, I would like to raise awareness about exhibitionism for all readers, especially Indonesian people. I hope after reading my screenplay, readers will be able to understand more about exhibitionism. My screenplay explores the struggle of an exhibitionist to repress his desire to exhibit and his effort to change into a “normal” person sexually through Peter, my main character. The story goes around Peter who is an exhibitionist that is struggling with his desire to expose his genital to his victims while he does not really accept his sexual deviation which resulted internal conflict inside him. Later, he meets a girl that he really likes which makes him motivated to change. He tries his best to change before the girl realizes that there is something else about him.